Urban Planning vs. Agricultural Production: A Study on the Po Valley - Francesco Zullo; Gianni Di Pietro; Chiara Cattani; Cristina Montaldi (Land, 2023)
At a time when wars and pandemics have disrupted the world order and deeply damaged international agreements, more people are talking about the energy and food independence of the nation-states. It is clear that the achievement of these objectives will not be rapid, but it is also clear that land use must take account of these important aspects. The over-dimensioning of the settled areas presents illogically in almost all municipal urban planning plans regardless of their geographical location, demographic dynamics, and values of the administered territory; it certainly constitutes an obstacle to effective land use. The work presented here aims to analyze the effects on agricultural production of the transformations envisaged by the plans of the provinces of Modena and Reggio nell’Emilia, while also providing solutions that could promote the sustainability of the interventions planned in these areas of high agri-food value.